Fabrication and characterization of high-speed oxide-confined vertical cavity surface emitting lasers - Al-Omari, Ahmad Nasser, author; Lear, Ken, advisor; Wilmsen, Carl, committee member; Field, Stuart, committee member (Colorado State University. Libraries, 2002)
The necessities for communication-network services such as database queries, remote education, telemedicine and videoconferencing have increased the need for highspeed communication systems with greater bandwidth. Faster single channel systems require faster VCSELs, and thus it is important to develop high-speed VCSELs, since they are suited for LAN application in a number of ways. High-Speed Oxide-Confined Vertical-Cavity Surface Emitting Lasers were fabricated in this research. Standard and repeatable fabrication steps were developed. Important fabrication steps that enhance the oxide-confined VCSELs modulation frequency were adopted. Photosensitive and non-photosensitive polyimides were investigated. Metal-to-polyimide adhesion was improved. Adhesion strength was examined using scotch tape. The measured threshold voltage and current of a fabricated VCSEL with 28μm diameter and 7μm oxide-confined aperture were as low as 1.5V and 0.4mA, respectively. The active area resistance at zero bias was found to be 98Ω. Optical modulation frequency of 17.0GHz for a VCSEL with 28μm diameter and 7μm oxide-confined aperture was observed. An equivalent circuit model for high-speed oxide-confined VCSELs, which is important for designing high-speed interfacing circuits to VCSELs, was obtained. Ion implanted VCSELs were investigated and simulated using the Trim and Pspice softwares. Eon implantation is expected to reduce the active area capacitance from 135fF to 83fF. As a consequence, the electrical –3dB frequency will increase to 32GHz, which represents about 30% improvement.
Covers not scanned. Item deaccessioned after digitization.
Keywords: Laser communication systems